Synergistic catalyst-support interactions in a graphene-Mn3O4 electrocatalyst for vanadium redox flow batteries - Ejigu, Andinet; Edwards, Matthew; Walsh, Darren A. (American Chemical Society, 2015)
The development of vanadium redox flow batteries (VRFBs) is partly limited by the sluggishness of the electrochemical reactions at conventional carbon-based electrodes. The VO2+/VO2+ redox reaction is particularly sluggish and improvements in battery performance require the development of new electrocatalysts for this reaction. In this study, synergistic catalyst-support interactions in a nitrogen-doped, reduced-graphene oxide/Mn3O4 (N-rGO- Mn3O4) composite electrocatalyst for VO2+/VO2+ electrochemistry are described. X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) confirm incorporation of nitrogen into the graphene framework during co-reduction of GO, KMnO4 and NH3 to form the electrocatalyst, while transmission electron microscopy (TEM) and XRD confirm the presence of ca. 30 nm Mn3O4 nanoparticles on the N-rGO support. XPS analysis shows that the composite contains 27% pyridinic N, 42% pyrrolic N, 23% graphitic N and 8% oxidic N. Electrochemical analysis shows that the electrocatalytic activity of the composite material is significantly higher than those of the individual components due to synergism between the Mn3O4 nanoparticles and the carbonaceous support material. The electrocatalytic activity is highest when the Mn3O4 loading is ~24% but decreases at lower and higher loadings. Furthermore, electrocatalysis of the redox reaction is only observed when nitrogen is present within the support framework, demonstrating that the metal-nitrogen-carbon coupling is key to the performance of this electrocatalytic composite for VO2+/VO2+ electrochemistry.